The Pleasure of Playing Less - Alharthi, Sultan A.; Toups Dugas, Phoebe; Alsaedi, Olaa; Tanenbaum, Theresa Jean; Hammer, Jessica (Play Story Press, 2026)
In this book, we explore the pleasure of playing less through a collective experience of playing the Kittens Game -- a self-described “Dark Souls of incremental gaming”. We draw on techniques of close reading and hermeneutics to ground our analysis and supplement our individual reflections on how these games incentivize players to play less and plan more.